2018
DOI: 10.2196/cancer.8430
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Group Intervention for Ovarian Cancer Survivors: Feasibility and Preliminary Results

Abstract: BackgroundDevelopment of psychosocial group interventions for ovarian cancer survivors has been limited. Drawing from elements of cognitive-behavioral stress management (CBSM), mindfulness-based stress reduction (MBSR), and acceptance and commitment therapy (ACT), we developed and conducted preliminary testing of an Internet-based group intervention tailored specifically to meet the needs of ovarian cancer survivors. The Internet-based platform facilitated home delivery of the psychosocial intervention to a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 50 publications
2
67
1
Order By: Relevance
“…It can be considered as an advantage of this study that the educational effect was persistent after three months of intervention. In other studies that have examined the impact of Web-based or Internet-based interventions on QoL of cancer survivors, social performance has not changed significantly after interventions [41][42][43]. Although these methods and social network-based methods are not ineffective and they have a high rate of patient participation due to their ease of access, one of their biggest challenges is low treatment adherence, which affects treatment effectiveness [19].…”
Section: Meanwhile Compen Et Al Compared the Effect Of Routine Treamentioning
confidence: 99%
“…It can be considered as an advantage of this study that the educational effect was persistent after three months of intervention. In other studies that have examined the impact of Web-based or Internet-based interventions on QoL of cancer survivors, social performance has not changed significantly after interventions [41][42][43]. Although these methods and social network-based methods are not ineffective and they have a high rate of patient participation due to their ease of access, one of their biggest challenges is low treatment adherence, which affects treatment effectiveness [19].…”
Section: Meanwhile Compen Et Al Compared the Effect Of Routine Treamentioning
confidence: 99%
“…Of the 16 studies, seven were conducted in the United States [26,32,36,37,[40][41][42], seven were conducted in mainland China [27][28][29][30][31]33,34], one was conducted in Canada [25,38], and one was conducted in Australia [35,39]. All studies were published between 2003 and 2019, and 75% (12/16) of the studies were published between 2016 and 2019 [27][28][29][30][31][32][33][34][35][39][40][41][42]. The majority of the patients recruited were highly educated (college or higher) in six studies [25,26,32,33,38,41,42].…”
Section: Resultsmentioning
confidence: 99%
“…1). The 18 articles were originally classified into ten quantitative [25][26][27][28][29][30][31][32][33][34], four qualitative [35][36][37][38], and four mixed-methods [39][40][41][42] study designs. Classen et al [25] and Wiljer et al [38] reported different findings from the GyneGals program, and Erfani et al [35] and Erfani et al [39] explored the different perspectives of the Ovarian Cancer Australia (OCA) Facebook.…”
Section: Search Outcomementioning
confidence: 99%
“…Lutgendorf focuses on ovarian cancer, another disease with a high mortality rate. Recently, she developed a web‐based intervention for these patients that attempts to provide them with better social support, enabling them to connect with one another online, learn meditation and stress management skills, and find meaning in their lives . Although her research is in its early stages, it is modeled after a program developed by Michael Antoni, PhD, director of the Center for Psycho‐Oncology Research at the University of Miami in Coral Gables, Florida.…”
Section: Interventions Seek To Reduce Stress In Patients With Cancermentioning
confidence: 99%
“…Recently, she developed a web-based intervention for these patients that attempts to provide them with better social support, enabling them to connect with one another online, learn meditation and stress management skills, and find meaning in their lives. 3 Although her research is in its early stages, it is modeled after a program developed by Michael Antoni, PhD, director of the Center for Psycho-Oncology Research at the University of Miami in Coral Gables, Florida. He and his colleagues also have performed extensive research in this area and demonstrated in a National Cancer Institute-funded randomized controlled trial that patients with nonmetastatic breast cancer who learned cognitive behavioral techniques such as muscle relaxation, deep breathing, and coping skills in the weeks after surgery had improved survival and a greater disease-free interval after undergoing the intervention.…”
Section: Interventions Seek To Reduce Stress In Patients With Cancermentioning
confidence: 99%